Progressive Judaism and the Bar Mitzvah: A Rites of Passage Ritual that Repositions the Mother in Her Sons’ Lives - Epstein, Sarah (Journal of the Motherhood Initiative for Research and Community Involvement, 2018)
Ritual is a way of acknowledging our relationship to each other, to our culture, to our community, and to our past. Ritual is also a way of reminding ourselves of what is important and who is important. I am the Jewish mother of two sons, both of whom have now been bar mitzvah. I am also the sole Jewish parent, and along with my husband, we are members of a progressive Jewish community in Melbourne, Australia. The progressive Jewish bar and bat mitzvah ritual offers a way to capture the deep movement and meaning of our lives as we transition from childhood to young adulthood. The bar/bat mitzvah process engenders individuation yet adheres the individual to community and others. However, traditional bar and bat mitzvah rites of passage are deeply gendered with separate roles ascribed to the mother and father depending on the gender of the child. Furthermore, patriarchal mother-son discourse marks the father as a crucial mentor through a boy’s transition to manhood. The mark of gender displaces the mother in relation to her son as he moves toward manhood. This paper draws on my personal experience to suggest that the progressive bar mitzvah process can both bind our sons to the Jewish community and their history, and help sanction a deep and powerful connection between mother and son.